Konseptualisasi Ontologi Iklan Website - Nuri Cahyono; Ema Utami; Armadyah Amborowati (Jurnal Buana Informatika, 2016)
Abstract. The high internet users in Indonesia, with a number of user penetration of more than 34.9%. The internet user has a diverse demographic that is spread throughout the territory. Seeing this potential can be in the know on the website advertising potential. To optimize that ads on a website can be relevant to the user required a design method. Ontologies are used as domain knowledge in the delivery of relevant ads. Ontology is built through a process of conceptualization, adapted from methods Gruninger and Fox and Methontology. Conceptualization resulting from such methods, evaluation methods OntoQA (Ontology Quality Analysis). Measurements were carried out to produce a quality score potential knowledge with details Relation richness value of 0.451, the value of Inheritance richness of 4.857 and a richness Attributte value of 6.75. Value Relations shows the richness of the information provided ontology categorized at level sufficiently rich in knowledge. Value Inheritance richness showed ontology includes areas of general knowledge. While the value Attributte describe the richness of the information provided.Keywords: Ontology, Ads, OntQA Abstrak. Tingginya pengguna internet di indonesia, dengan jumlah penetrasi pengguna lebih dari 34,9%. Pengguna internet tersebut memiliki demografi beraneka ragam yang tersebar diseluruh wilayah. Melihat hal tersebut dapat di ketahui potensi iklan pada website sangat potensial. Untuk mengoptimalkan agar iklan yang ada pada sebuah website dapat relevan dengan pengguna diperlukan sebuah metode perancangan. Ontologi dimanfaatkan sebagai domain pengetahuan dalam pemberian iklan yang relevan. Ontologi dibangun melalui proses konseptualisasi yang diadaptasi dari metode Gruninger and Fox dan Methontology. Konseptualisasi yang dihasilkan dari metode tersebut, dilakukan evaluasi menggunakan metode OntoQA (Ontology Quality Analysis). Pengukuran yang dilakukan menghasilkan skor kualitas potensi pengetahuan dengan rincian nilai Relation Richness sebesar 0,452, nilai Inheritance Richness sebesar 4,857 dan nilai Attributte Richness sebesar 6,75. Nilai Relation Richness menunjukkan informasi yang disediakan ontologi dikategorikan pada level cukup kaya akan pengetahuan. Nilai Inheritance Richness menunjukkan ontologi mencakup bidang pengetahuan yang umum. Sementara nilai Attributte Richness menggambarkan informasi yang disediakan.Kata Kunci: Ontologi, Iklan, OntoQA